Kedudukan Ilmu Pengetahuan (Sains) dan Agama dalam Perspektif Muhammad Abduh dan Blaise Pascal - Thori Maulana Suhendi (Gunung Djati Conference Series, 2023)
This study aims to discuss the position of science (science) and religion in the perspective of Muhammad Abduh and Blaise Pascal. This study uses a qualitative method by applying a descriptive-analytical method. The analytical knife of this research is the perspective of Muhammad Abduh and Blaise Pascal, while the objects studied are the position of science and religion. The results and discussion in this study show that the position of science and religion in the perspective of Muhammad Abduh offered a solution through the opening up of Islam and its people in accepting change and modern science. Meanwhile, Blaise Pascal said that reason is not the only instrument in gaining knowledge, but faith and heart can also answer human problems. The conclusion of this research is that both Muhammad Abduh and Blaise Pascal in looking at the position of science indicate the alignment of the application of science and religion in overcoming the problems of human life.